The reference to plurilegislative systems ad intra concerns the analogical application of Article 9.10 of the Spanish Civil Code to determine the applicable law for foreigners. Supreme Court Judgment of 19 May 2025: la aplicación analógica del artículo 9.10 CC para determinar la ley aplicable a los extranjeros. Sentencia del Tribunal Supremo de 19 de mayo de 2025 - Goñi Urriza, Natividad (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The Supreme Court’s decision rightly resolves the complicated problem of applying the conflict rule known as ‘remisión ad intra por reenvío de retorno’. Adopting the solution of applying Article 9.10 CC by analogy, which establishes the law of habitual residence as the personal law of the subjects who do not have nationality to determine, in an internal conflict of laws, the governing law of the succession of a foreigner, puts an end to the doctrinal discussion in Spain on this matter. This approach strikes a balance between the various Spanish civil laws and the principle of proximity, which is a fundamental principle of private international law.